ANALISIS KUAT TEKAN BETON DENGAN LIMBAH SERABUT KELAPA SEBAGAI BAHAN TAMBAH - Urfan (Universitas Bina Taruna Gorontalo, 2025)
This study aims to examine the use of coconut fiber waste as an additive in concrete mixtures for rural road pavements. The construction of road infrastructure and buildings requires materials that are not only strong and durable, but also affordable and environmentally friendly. Coconut fiber was chosen because it is an abundant organic waste, lightweight, and has mechanical properties that can improve concrete performance. The method used in this study is a laboratory experiment with a variation of coconut fiber addition of 5% of the cement weight. The tests carried out include compressive strength tests at the age of 3, 7, 14, 21, and 28 days. The results of the study indicate that the addition of coconut fiber in high amounts tends to reduce the compressive strength of the concrete, not meeting the planned and it can also be seen that there are 3 test objects that are damaged and cannot be tested for compression so that they get a result of 0. and do not support the concept of sustainable development